Minimal Detection of Cerebrospinal Fluid Escape After Initiation of Antiretroviral Therapy in Acute HIV-1 Infection - HANDOKO, Ryan (AIDS, 2021)
OBJECTIVE: Despite suppression of HIV-1 replication in the periphery by antiretroviral therapy (ART), up to 10% of treated individuals have quantifiable HIV-1 in the CSF, termed CSF escape. CSF escape may be asymptomatic but has also been linked to progressive neurological disease, and may indicate persistence of HIV in the central nervous system (CNS). CSF escape has not yet been assessed after initiation of ART during acute HIV-1 infection (AHI). DESIGN: Prospective cohort study. SETTING: Major voluntary counseling and testing site in Bangkok, Thailand. SUBJECTS: Participants identified and initiated on ART during AHI who received an optional study lumbar puncture at pre-ART baseline or after 24 or 96 weeks of ART. MAIN OUTCOME MEASURES: Paired levels of CSF and plasma HIV-1 RNA, with CSF > plasma HIV-1 RNA defined as CSF escape. RESULTS: 204 participants had paired blood and CSF sampling in at least one visit at baseline, week 24, or week 96. 29 participants had CSF sampling at all three visits. CSF escape was detected in 1/90 at week 24 (CSF HIV-1 RNA 2.50 log(10) copies/mL, plasma HIV-1 RNA < 50 copies/mL), and 0/55 at week 96. CONCLUSIONS: While levels of CSF HIV-1 RNA in untreated AHI are high, initiating treatment during AHI results in a very low rate of CSF escape in the first two years of treatment. Early treatment may improve control of HIV-1 within the CNS compared to treatment during chronic infection, which may have implications for long-term neurological outcomes and CNS HIV-1 persistence.